The role of the product owner in digital communication in agile environments: A case study of Initgrammers - Nina, Aguiar Mariño; Sevilla, Alessandro Sebastián Sierra; Rojas, Giullyana Karina Galeas (Edelweiss Applied Science and Technology, 2025)
This article examines the role of the Product Owner (PO) in digital communication within agile environments, using InitGrammers as a case study. It emphasizes that the PO serves as a crucial intermediary between the development team and the client, facilitating communication and ensuring the achievement of project objectives. The primary goal of the research is to understand how the digital tools and strategies employed by the PO contribute to project success. The research hypothesis centers on how the PO can optimize communication within development teams and overcome challenges in digital environments. To achieve this, a qualitative methodology is utilized, including direct observation, semi-structured interviews, and interview analysis. The findings reveal that the PO relies not only on digital tools such as Jira, Discord, and Slack but also on effective team interaction, enabling coordinated and efficient task management. This fosters teamwork and supports the accomplishment of project goals. In conclusion, the study underscores that the PO’s role extends beyond technical responsibilities by incorporating strategic and communication skills, as well as a remarkable ability to adapt to various challenges in digital environments. It also highlights the effective use of agile tools and methodologies, which help align the team with the client’s objectives, enhancing both productivity and client satisfaction.